Pemanfaatan Google Sites sebagai Strategi Promosi Digital UMKM Roti Tenong Cabang Pasar Baru - Aisyah Rendini; Nurul Hikmah Farisy; Sularno Sularno; Zulfitri Yani (CV. ITTC INDONESIA, 2025)
This study discusses the use of Google Sites as a digital promotion strategy for the Pasar Baru branch of Roti Tenong MSME. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results show that the implementation of Google Sites makes it easier for business actors to display their profiles, product catalogs, and contact information professionally. In addition, this site contributes to increasing consumer interest and ease of access to product information online. The use of Google Sites is also considered efficient because it does not require high creation and maintenance costs. Based on the results of the study, it can be concluded that Google Sites is an effective, practical, and relevant alternative solution for MSMEs in developing digital promotion strategies in the current era of technological transformation.